Indigenous disability studies
1 online resource (xxi, 333 pages)
Keywords: "This book provides a comprehensive approach to the perspectives, lived experiences, and socio-cultural beliefs of Indigenous scholars regarding disabilities through a distinctions-based approach. Indigenous people demonstrate considerable knowledge in a multitude of compacities in spite of legal, monetary, social, economic, health, and political inequalities that they experience within from administrative authorities whether health, education or governments. By include various knowledge systems related to: social-cultural, traditional governance, spirituality, educational, and self-representation within a communal understanding, the knowledge brought forth will be a combination of information from within/communal and outwards/infusion by Indigenous teachers, scholars, academics, and professionals who aim to combat the negative effects of disability labels and policies that have regulated Indigenous peoples. Comprised of five sections: -The power, wisdom, knowledge, and lived experiences of Elders -Reframing the narrative - Navigating self- representation -Learning from within - Including traditional knowledge -Challenging colonial authority - Infusing regional ideals and concepts -Interpretations, narratives, and lived experiences of grassroots teachers and social service providers it will be an asset to those who seek out a deeper understanding of the complexity of Indigenous people and their knowledge who deal with predominantly non-Indigenous mindsets and barriers to education. Courses on disability studies, indigenous studies, social work, health, education and development studies will all benefit from this book"--